Agricultural land conversion for housing development and sustainable food agricultural land - Saputra, Rodhi Agung; Tisnanta, HS; Sumarja, FX; Triono, Agus (Technium Social Sciences Journal, 2022)
This research is to examine related to land acquisition for housing development and the importance of legal protection for sustainable food agricultural land. The main development development is the factors that increase the population, which means the number of needs becomes greater, one of which is the need for land. Because most of Indonesia's population is in the field of livelihood, the arable land is getting narrower because agriculture will be used to save money, roads, industry and others. This is intended so that the area of agricultural land for food does not continue to shrink every year. Responding to the conversion of sustainable agricultural land and to ensure the consistency of the availability of replacement land as a result of land conversion, such as the formulation of input for approval for the presence of free land provided. This is necessary to maintain as well as the availability of the converted free facilities. The problem that will be discussed in this study is how the regulation of land acquisition for development development is related to the guarantee of sustainable agricultural land. The research method used is a normative research method with a statute approach and analyzed using content analysis.